COMPARATIVE ASSESSMENT OF THERAPEUTIC POTENTIAL OF VACHADI AND HINGWADI GHTRITA IN PATIENTS OF DEPRESSION - Madhuri, Pawar; Asmita, Wele (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: Present exploratory clinical study dealt with comparative assessment of therapeutic effect of medicated ghee formulations i.e. Vachadi [VG] and Hingwadi Ghrita [HG] in patients of mild to moderate depression. Methods: Open label nonrandomized standard controlled clinical trial was carried out. Using Hamilton scale test total twelve patients of mild to moderate depression were grouped in two groups[A and B]. Patients of group A and group B received HG and VG along with standard antidepressants respectively for sixty days. Pre, mid and post HAMD scores of both group patients were recorded and compared. Data was analyzed with Friedman and Mann Whitney statistical test. Results: Statistical analysis showed a significant gradual change in HAMD values for both study groups after sixty days of treatment [P< 0.05]. However, when pre and post HAMD scores of both groups are statistically analyzed, Hingwadi Ghrita demonstrated significant positive result in reduction of HAMD scores compared to Vachadi Ghrita [P=0.003]. Beneficial effects on patients appetite, bowel movement was seen for both group patients. Conclusion: Thus it is concluded that along with antidepressants Hingwadi Ghrita would be the better choice as an adjuvant drug than Vachadi Ghrita for mild to moderate depression patients. More studies with larger number should be done to validate this result.